2010
DOI: 10.5897/ajb2010.000-3021
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of industrial chemicals on fish fingerlings (Tilapia guineensis)

Abstract: Tilapia guineensis commonly found in the Niger Delta ecological zone of Nigeria was exposed to sublethal concentrations (1.56, 3.13 mg/l) of neatex (industrial detergent) and norust CR 486 (corrosion inhibitor) using the Organisation for Economic Cooperation and Development (OECD) # 203 protocol. At test termination on the 28th day, the rate of bioaccumulation of surfactants in the fish gills, gut and muscle tissues were measured. The levels of surfactant in the gills, gut and muscle tissues were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…Other studies which showed similar comparison include the research works by several other Authors. [9][10][11]18,[34][35][36][37][38][39] Soil organisms enhance soil aggregation and porosity, thus increasing infiltration and reducing runoff. Earthworms are an important component of the soil system, and can enhance plant growth by improving soil fertility and nutrient recycling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies which showed similar comparison include the research works by several other Authors. [9][10][11]18,[34][35][36][37][38][39] Soil organisms enhance soil aggregation and porosity, thus increasing infiltration and reducing runoff. Earthworms are an important component of the soil system, and can enhance plant growth by improving soil fertility and nutrient recycling.…”
Section: Discussionmentioning
confidence: 99%
“…All these could subsequently lead to reduction as well as extinction of some vital species. [5][6][7][8][9] Industrial chemicals (demulsifiers, corrosion inhibitors and dispersants) mainly of surfactant-based commonly used by industrial petroleum operators may cause environmental problems including the toxicity of the surfactants to fish and invertebrates, foaming and euthrophication. 10,11 A foaming agent is a material that facilitates formation of foam such as a surfactant.…”
Section: Impacts Of Acute Exposure Of Industrial Chemicals and Pesticmentioning
confidence: 99%
See 1 more Smart Citation
“…Surfaktan merupakan salah satu bahan yang dapat dimanfaatkan diberbagai bidang kehidupan, baik di bidang industri, makanan, rumah tangga, kosmetik dan farmasetika (Ogeleka et al, 2010). Surfaktan merupakan bahan aktif yang unik karena mempunyai sisi hidrofobik dan sisi hidrofilik, dan mampu berinteraksi dengan pelarut sehingga dapat menurunkan tegangan permukaan (Knepper et al, 2003).…”
Section: Pendahuluanunclassified
“…Metode spektrofotometri juga banyak digunakan untuk analisis surfaktan anionik. Analisis secara spektrofotometri dapat dilakukan dengan menggunakan pereaksi methylene blue (Ogeleka et al, 2010), ethyl violet (Yamamoto and Motomizu, 1987), rhodamine B dan rhodamine 6G (Tajalli et al, 2009), dan acridine orange ( Adak et al, 2005). Terdapat beberapa kekurangan dalam analisis surfaktan anionik dengan metode dan pereaksi tersebut, yaitu bahan yang kurang ramah lingkungan dan biaya operasionalnya mahal.…”
Section: Pendahuluanunclassified